(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
This article examines the Unity-Based Peace Education approach as a new solution to the conflict in Cyprus between Turkish and Greek communities. This approach may be helpful to the conflicting parties on the island with its premise that peace building can be reached and practiced through ‘building unity’. This assertion makes the Unity-Based Peace approach unique among other peace/conflict resolution methods. In the first part, the Cyprus conflict will be explained briefly. In the second part, the paper will provide a presentation of the Unity-Based Peace approach and its comprising programs. The paper will conclude with an assessment of possible implications arising from the application of the Unity-Based Peace programs to the Cyprus conflict.